2023
DOI: 10.3390/en16041704
|View full text |Cite
|
Sign up to set email alerts
|

Concerns on Full Electric Mobility and Future Electricity Demand in Italy

Abstract: This work aims to provide an energy and critical analysis of the new “ecological scenario” that sees the world shift the transport sector from the classic fossil-fueled traction towards a purely electric traction. Is it a transition to a cleaner and more environmentally friendly world? This is the central question we need to answer. In this context of forced electrification of passenger vehicles, the authors estimated the electricity surplus needed in Italy to face this transition with a projection up to 2050,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The average amounts of cerium present in CATCONS vary for specific vehicle categories, which can be classified into 3 groups (Figure 1): The 2012 sedan model exemplifies the inclusion of REEs in vehicles. This particular vehicle was found to contain around 0.44 kg of REEs, with 0.4 kg integral to the vehicle's fundamental functions including safety components and the basic radio/speaker system, and 0.04 kg designated for additional features such as the navigation system, DVD player, and electrically controlled seats [62]. However, hybrid vehicles, specifically those equipped with a nickel-metal hydride battery, demonstrate a higher REE of over 3.5 kg [63].…”
Section: Battery Electric Vehiclesmentioning
confidence: 99%
“…The average amounts of cerium present in CATCONS vary for specific vehicle categories, which can be classified into 3 groups (Figure 1): The 2012 sedan model exemplifies the inclusion of REEs in vehicles. This particular vehicle was found to contain around 0.44 kg of REEs, with 0.4 kg integral to the vehicle's fundamental functions including safety components and the basic radio/speaker system, and 0.04 kg designated for additional features such as the navigation system, DVD player, and electrically controlled seats [62]. However, hybrid vehicles, specifically those equipped with a nickel-metal hydride battery, demonstrate a higher REE of over 3.5 kg [63].…”
Section: Battery Electric Vehiclesmentioning
confidence: 99%
“…1. Need for an increase in the electricity produced (see Falfari et al [3]) and the creation of a capillary infrastructure capable of bringing the necessary power to every part of Europe. In [3], the authors found that, in 2050, the surplus of electricity to be produced compared to the current production in Italy (year 2021) will be equal to +27.6 %.…”
Section: Present Workmentioning
confidence: 99%
“…Need for an increase in the electricity produced (see Falfari et al [3]) and the creation of a capillary infrastructure capable of bringing the necessary power to every part of Europe. In [3], the authors found that, in 2050, the surplus of electricity to be produced compared to the current production in Italy (year 2021) will be equal to +27.6 %. Furthermore, the demand for electricity availability is concentrated in specific time slots for both domestic and industrial uses (including the need to recharge electric vehicles).…”
Section: Present Workmentioning
confidence: 99%
See 2 more Smart Citations